2021
DOI: 10.21203/rs.3.rs-345932/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superlubric Polycrystalline Graphene Interfaces

Abstract: The effect of corrugated grain boundaries on the frictional properties of extended graphitic contacts incorporating a polycrystalline surface are investigated. The friction is found to be dominated by shear induced buckling and unbuckling of corrugated grain boundary dislocations, leading to a nonmonotonic behavior of friction with normal load and temperature. The underlying mechanism involves two competing effects, where an increase of dislocation buckling probability is accompanied by a decrease of the dissi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…These results have important implications for understanding and improving the wear resistance of SL-MoS 2 with GB defects. Gao et al [972] investigated the effect of corrugated GB on the tribological properties of extended planar graphite contacts containing polycrystalline surfaces through molecular dynamics simulations. It is found that dynamic friction is mainly affected by shear-induced buckling and debuckling of corrugated GB dislocations, resulting in non-monotonic behavior of friction under normal loads and temperatures.…”
Section: Simulation In Micro-friction and Superlubricitymentioning
confidence: 99%
“…These results have important implications for understanding and improving the wear resistance of SL-MoS 2 with GB defects. Gao et al [972] investigated the effect of corrugated GB on the tribological properties of extended planar graphite contacts containing polycrystalline surfaces through molecular dynamics simulations. It is found that dynamic friction is mainly affected by shear-induced buckling and debuckling of corrugated GB dislocations, resulting in non-monotonic behavior of friction under normal loads and temperatures.…”
Section: Simulation In Micro-friction and Superlubricitymentioning
confidence: 99%